A model of community empowerment in an effort to improve welfare by the ceria learning house community in sungai pedado village, Keramasan Village, Palembang City - Nurali Utami; Alfitri Alfitri; Ardiyan Saptawan (Institute of Computer Science (IOCS), 2023)
The study in this research tries to find out how the community empowerment process is in an effort to improve welfare and empowerment models in an effort to increase welfare by the Ceria Learning House community. Researchers used a qualitative descriptive approach in this study. The conclusions that the researchers formulated in this study are that in practice, the community empowerment process in Sungai Pedado village includes 3 stages of empowerment, namely; awareness stage, capacity building stage and empowerment stage. In the community awareness stage, RBC was able to increase public awareness through socialization by conveying empowerment program activities marked by the increased participation of the Sungai Pedado village community as members of the empowerment group.